Clinical characteristics and prognostic factors in patients with breast cancer and leptomeningeal metastases from a large registry of BMBC - Elena Laakmann; Marcus Schmidt; Kristina Lübbe; Elisa Agostinetto; Mette van Ramshorst; Thomas Decker; Wolfram Malter; Francesco Schettini; Mario Fontes Sousa; Carsten Denkert; Tanja Neunhöffer; Leonor Matos; et al. (Breast)
Background: Leptomeningeal metastases (LM) in patients with breast cancer (BC) are associated with a dismal prognosis. We explored clinical characteristics and prognostic factors in patients with BC and LM in the German Brain Metastases in Breast Cancer Registry. Methods: All patients with histologically confirmed BC and diagnosis of LM (defined as the presence of tumor cells in the cerebrospinal fluid, or presence of typical clinical symptoms in combination with typical magnetic resonance imaging findings) were included. Results: A total of 3857 patients were included in the analysis (n = 859 (22.3 %) with LM). Among patients with LM a median progression-free survival was 4.2 months (95 % CI 3.6–4.8), and median overall survival was 5.7 months (95 % CI 4.9–6.7). In the multivariate analysis older age ( ≥ 60 vs. <60 years, Hazard ratio (HR): 1.65, 95 %CI: 1.25–2.18), worse performance status (ECOG 2–4 vs. 0–1 HR: 2.15, 95 %CI: 1.63–2.82), hormone receptor positive/HER2-negative (HR+/HER2-) or triple-negative subtype (HR: 1.54 95CI%: 1.07–2.23 and HR: 1.87, 95 %CI: 1.25–2.81), and higher number of BM (2–3 vs. 1, HR: 1.49, 95 %CI: 1.05–2.11 4) were significantly associated with a higher risk of death. Stereotactic radiotherapy (HR 0.49 95 %CI 0.30–0.79) and whole brain irradiation (HR: 0.58, 95 %CI: 0.42–0.80), endocrine therapy in patients with HR + BC (HR: 0.31, 95 %CI: 0.21–0.45) as well as HER2-targeted therapy for patients with HER2+ BC (HR 0.41, 95 %CI: 0.25–0.68) were associated with a significantly longer survival. Conclusions: Clinicopathological factors associated with survival can help clinicians identify patients who are candidates for treatment (de)escalation in clinical trials.